Y chromosome evidence confirms northeast Asian origin of Xinjiang Kazakhs and genetic influence from 18th century expansion of Kerey clan - Wang, Bangyan; Liang, Jiayu; Allen, Edward; Chang, Xin; Jiang, Zixi; Yu, Yao; Shi, Meisen; Wen, Shaoqing (Frontiers in Ecology and Evolution, 2023)
The Kazakhs of Xinjiang province are characterized by their nomadic lifestyle and patrilineal clan system. However, compared to Central Asian Kazakhs, a lack of Y chromosomal high-resolution analysis has hindered our understanding of the paternal history of modern Xinjiang Kazakhs. In this study, we present the analysis of 110 Y-SNP data from 209 Altay Kazakhs and 201 Ili Kazakhs in Xinjiang, along with their previously reported 24 Y-STR loci data. We found that the Y chromosome haplogroups exhibit greater diversity in Altay Kazakhs compared to Kazakhs in Kazakhstan, Russia, and other regions of China. Y-SNP-based PCA plots reveal that both the Altay and Ili Kazakhs are situated between the Turkic, Mongolia, and Tibeto-Burman clusters. The dominant haplogroup C2a1a3-F1918, which originated in northeast Asia during the Neolithic Age, accounts for nearly half of the Altay and Ili Kazakhs. The Y lineage network of C2a1a3-F1918 contained two subclusters. Approximately 60.6% of the Altay Kazakhs belong to the DYS448-23 subcluster, indicating their Kerey-Abakh ancestry. On the other hand, around three-quarters of the Ili Kazakhs belong to the DYS448-22 subcluster, suggesting their Kerey-Ashmaily heritage. Notably, the TMRCA ages of the DYS448-23 subcluster were calculated to be 289.4±202.65 years, which aligns with the historical immigration of the Kerey clan back to the Altay Mountains after the defeat of the Dzungar by the Qing dynasty in the mid-18th century.